Tailoring and probing the electrical and optical properties of atomically thin two-dimensional materials - Peimyoo, Namphung (2016)
Two-dimensional (2D) materials, such as graphene and transition metal dichacogenides (TMDs), have received considerable interest, owing to their remarkable properties. Such new 2D materials are promising candidates to be developed as alternatives of silicon for the integrated circuit technology and III-V semiconductors for optoelectronic and photonic applications. In this thesis, optical spectroscopies and electrical transport measurements have been used to investigate and manipulate the intrinsic optical, electrical and thermal properties of these newly emerged 2D materials. On the one hand, graphene as the first 2D semimetal has aroused great attention due to its attracting properties such as quantum hall effect and ballistic conduction at room temperature. Here, controllable tailoring of charge carrier density graphene layers by integrated with azobenzene molecules has been achieved via the chemical doping. Experimentally, Raman spectroscopy has been utilized to monitor the doping levels in mono- and few-layer graphene. The observed chemical doping effect and surface enhanced-Raman scattering have exhibit distinct thickness- dependent characteristics, in which the strongest effects are uncovered in monolayer. It is attributed to the different charge transfer due to thickness-dependent screening effect. In addition, by taking the advantage from the unique nature of azobenzene, i.e. the reversible transformation of configurations under the UV light, we are able to optically modulate the electrical property and charge density in graphene, which has been well explained by our theoretical simulations. These studies pave the way of development of graphene as photoswitch and nanoelectronic devices by use of reversible chemical doping.